Kansas Field Research 2023 (Kansas Agricultural Experiment Station Research Reports, 2023)
A summary of research conducted in 2021-2023 on field production and management practices for crops in Kansas. Published in 2023 from the Kansas State University Agricultural Experiment Station and Cooperative Extension Service.https://www.ag.k-state.edu/
Keywords: canola; corn; tillage; sorghum; rye; management practices; soybean; Kansas weather; weed science; wheat; planting dates; tiller yield; cover crops; soil properties; soil evaporation; residue cover; nitrogen management; fungicide management; seeding rate; seed cleaning